Riding the tiger: civilian control and the military in democratizing Korea - Croissant, Aurel (Armed forces & society, 2004)
For many young democracies, the institutionalization of civilian control over the military is a crucial task for democratic consolidation. This is especially true for South Korea. After Korea gained independence in 1948, the military was the most powerful player in Korean politics. However, in the 1990s, the pattern of civil-military relations changed dramatically from military dominance over civilian politics to civilian supremacy over the military. This article explores the dynamics of the institutionalization of civilian control in South Korea in four steps. In the first part, the study clarifies the concept of civilian control. The second part formulates an analytical frame of favorable and unfavorable conditions for successful institutionalization of civilian control. Thereafter the evolution and state of civil-military relations in South Korea before and after democratization is illuminated. Finally, some conclusions are drawn about why civilian control successfully became institutionalized in democratizing Korea.
Gesehen am 26.03.2021